algebraic formula a^2-b^b2
Answers
Answered by
1
❤️_______
________❤️
✌️_______UR ANSWER_______✌️
We know that
(a + b)^2 = a^2 + b^2 + 2ab
(a - b)^2 = a^2 + b^2 - 2ab
So, a^2 + b^2 formula can be
a^2 + b^2 = (a + b)^2 - 2ab
a^2 + b^2 = (a - b)^2 + 2ab
Algebra Formulas.
⤴️_____HOPE HELP YOU_____⤴️
✌️_______UR ANSWER_______✌️
We know that
(a + b)^2 = a^2 + b^2 + 2ab
(a - b)^2 = a^2 + b^2 - 2ab
So, a^2 + b^2 formula can be
a^2 + b^2 = (a + b)^2 - 2ab
a^2 + b^2 = (a - b)^2 + 2ab
Algebra Formulas.
⤴️_____HOPE HELP YOU_____⤴️
Answered by
2
Algebraic formula of a^2-b^2 is
![a {}^{2} - b {}^{2} = (a + b)(a - b) a {}^{2} - b {}^{2} = (a + b)(a - b)](https://tex.z-dn.net/?f=a+%7B%7D%5E%7B2%7D++-+b+%7B%7D%5E%7B2%7D++%3D+%28a+%2B+b%29%28a+-+b%29)
Similar questions